PEMBERDAYAAN SISWA SMA MELALUI PENGOLAHAN POPCORN KELOR DAN STIK KELOR DENGAN DIGITAL BRANDING UNTUK MENINGKATKAN KEWIRAUSAHAAN DAN PEMASARAN PRODUK LOKAL - Handris, Handris; Naim, Ifin; Mariani, Mariani; Lajaria, Ridha Taurisma; Suprianto, Ghalib; Patulak, Lucia Evianti; Sudarsana, I Wayan (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This activity aims to provide an understanding of business development based on marketing strategies. Marketing strategy is a crucial aspect for Moringa Popcorn and Moringa Stick producers to achieve business goals, especially in the face of competition. Business development requires the implementation of a marketing mix encompassing Product, Price, Promotion, and Place/Distribution. These four elements play a role in directing marketing activities to be more effective and increase product competitiveness. This community service activity was conducted at SMAN 20 South Konawe, Southeast Sulawesi Province, over two months through outreach and workshops. Participants included 25 teachers and students, supported by 7 university students and 10 lecturers from the Faculty of Economics and Business. The methods used included participatory learning, mentoring, and hands-on practice. Evaluation results showed a positive response from participants. They considered the marketing strategy material, covering product, price, distribution, and promotion, very useful and able to increase motivation in developing the business and supporting family economic growth.